In Silico Modeling of Itk Activation Kinetics in Thymocytes Suggests Competing Positive and Negative IP4 Mediated Feedbacks Increase Robustness - Mukherjee S. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0073937